2020
DOI: 10.3389/fonc.2020.01028
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Early Changes of Circulating Tumor DNA in the Plasma of Rectal Cancer Patients Receiving Neoadjuvant Concomitant Chemoradiotherapy: Evaluation for Prognosis and Prediction of Therapeutic Response

Abstract: Introduction: Patients with locally advanced rectal cancer (LARC) are undergoing neoadjuvant chemoradiotherapy (NCRT) prior to surgery. Although in some patients the NCRT is known to prevent local recurrence, it is also accompanied by side effects. Accordingly, there is an unmet need to identify predictive markers allowing to identify non-responders to avoid its adverse effects. We monitored circulating tumor DNA (ctDNA) as a potential liquid biopsy-based biomarker. We have investigated ctDNA change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 55 publications
0
47
1
Order By: Relevance
“…Among early studies, elevated baseline cfDNA has demonstrated feasibility (albeit total cfDNA and not ctDNA) to predict for tumor response or recurrence risk following neoadjuvant long-course chemoradiation in LARC [ 59 , 60 ]. Several other groups have shown an association between pre-chemoradiation ctDNA status and recurrence risk in LARC as well [ 52 , 61 ].…”
Section: Prediction Of Response To Neoadjuvant Therapy In Locally Advanced Rectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Among early studies, elevated baseline cfDNA has demonstrated feasibility (albeit total cfDNA and not ctDNA) to predict for tumor response or recurrence risk following neoadjuvant long-course chemoradiation in LARC [ 59 , 60 ]. Several other groups have shown an association between pre-chemoradiation ctDNA status and recurrence risk in LARC as well [ 52 , 61 ].…”
Section: Prediction Of Response To Neoadjuvant Therapy In Locally Advanced Rectal Cancermentioning
confidence: 99%
“…In mCRC, ctDNA status following metastasectomy or radical surgery is also recognized as a pivotal timepoint of ctDNA assessment and is the focus of ongoing clinical trials exploring intensified systemic therapies ( Table 4 ). In the neoadjuvant treatment of LARC, chemoradiation induces a strong reduction and even complete elimination of ctDNA by the end of the first week, while ctDNA levels were reduced regardless of eventual outcome [ 52 ]. A better understanding of the temporal dynamics of ctDNA release and clearance may be essential for the long-awaited applicability of ctDNA to predict for treatment response in the neoadjuvant treatment of LARC.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Numerous studies have explored what predicts a good response, or a pCR at surgery [4,[12][13][14][15][16][17][18][19][20][21]. However, these studies have thus far been unsuccessful in detecting any clinically useful marker for response prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies have explored the predictive capability of specific characteristics identified with magnetic resonance imaging (MRI) [22], presently used for routine staging. Numerous molecular properties of the rectal tumors have also been explored, usually in rather small cohorts, and although many published studies claim that a particular biomarker is promising, none have yet been sufficiently effective, as stated in multiple reviews [14][15][16]23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pazdirek et al [88] investigated changes in ctDNA levels of 36 patients with LARC undergoing neoadjuvant CRT and their relationship to treatment response. Positive ctDNA at baseline was associated with lower DFS and OS at 1.47 and 1.41 years respectively (p = 0.015 and p = 0.010, respectively).…”
Section: Locally Advanced Rectal Cancer (Larc)mentioning
confidence: 99%